2022
DOI: 10.53730/ijssh.v6n1.3528
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of fiber intakes with incidence of constipation in the elderly

Abstract: Constipation becomes one of the diseases that are often suffered by the elderly, many factors that affect constipation one of which is fiber intake. The goal of the study was to find out the relationship of fiber intake with the incidence of constipation in the elderly (elderly). The research is conducted with a cross-sectional approach.  The number of samples in the study as many as 65 elderly, sampling using purposive sampling techniques. The majority of research results obtained fiber intake of fewer than 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The results of PCR analysis to detected the presence gene of PelA gene (118bp) among of P. aeruginosa 9/10(90%) P.fluorescens 3/4(75%) . P.putadia 3/4(75%),isolates revealed that 15/18 (83.33%) of isolates were contain pelA gene (figure [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Pseudomonas spp can use either psl or pel as the primary biofilm matrix polysaccharide (Overhage et al, 2005).…”
Section: Detection Of Pela Genementioning
confidence: 99%
See 2 more Smart Citations
“…The results of PCR analysis to detected the presence gene of PelA gene (118bp) among of P. aeruginosa 9/10(90%) P.fluorescens 3/4(75%) . P.putadia 3/4(75%),isolates revealed that 15/18 (83.33%) of isolates were contain pelA gene (figure [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Pseudomonas spp can use either psl or pel as the primary biofilm matrix polysaccharide (Overhage et al, 2005).…”
Section: Detection Of Pela Genementioning
confidence: 99%
“…Pseudomonas spp can use either psl or pel as the primary biofilm matrix polysaccharide (Overhage et al, 2005). [23] Figure (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17): Ethidium bromide-stained agarose gel electrophoresis of PCR products of P. aeruginosa(1-11) P.fluorescens (12)(13)(14)(15)(16)(17)(18). P.putadia (19)(20)(21)(22)(23) .using primer pelA gene (118bp).…”
Section: Detection Of Pela Genementioning
confidence: 99%
See 1 more Smart Citation
“…4 The urinary calculi are formed by 70% of calcium, 20% of uric acid, 10% of magnesium ammonium phosphate (struvite) and about <1% of cystine. 5,6 Urine is a stable solution and any variation in the degree of saturation, of the urinary pH and of the concentration of crystallization inhibitors can alter the existing equilibrium and result in urolithiasis. 7 Considering this, we performed present study to assess clinical findings and management of bladder calculus in patients visiting VMKVMC hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Appearance of AMH is highest during folliculogenesis's recruitment stage, in the preantral and small antral follicles (10). This production decreases as follicles increase and enter selection stage, this results in a rise in FSH expression (11).…”
Section: Introductionmentioning
confidence: 99%